Oral Administration of Rosa gallica Prevents UVB−Induced Skin Aging through Targeting the c−Raf Signaling Axis - Seongin Jo (MDPI AG, 2021)
Rosa gallica is a widely used Rosa species for medicinal and culinary purposes. Rosa gallica has been reported to display antioxidant, anti−inflammatory, and antibacterial activities. However, the effect of Rosa gallica against skin aging in vivo is unknown and its active components have not been fully understood. Oral administration of Rosa gallica prevented UVB−mediated skin wrinkle formation and loss of collagen/keratin fibers in the dorsal skin of mice. Examination of biomarkers at the molecular level showed that Rosa gallica downregulates UVB−induced COX−2 and MMP−1 expression in the skin. Through a direct comparison of major compounds identified using the UHPLC−MS/MS system, we discovered gallic acid as the primary component contributing to the anti-skin aging effect exhibited by Rosa gallica. Examination of the molecular mechanism revealed that gallic acid can potently and selectively target the c−Raf/MEK/ERK/c−Fos signaling axis. In addition, both gallic acid and MEK inhibitor blocked UVB−induced MMP−1 expression and restored collagen levels in a reconstructed 3D human skin model. Collectively, Rosa gallica could be used as a functional ingredient in the development of nutraceuticals against skin aging.